Tackling the widespread and critical impact of batch effects in high-throughput data - Leek, Jeffrey T.; Scharpf, Robert B.; Bravo, Héctor Corrada; Simcha, David; Langmead, Benjamin; Johnson, W. Evan; Geman, Donald; Baggerly, Keith; Irizarry, Rafael A. (Nature reviews. Genetics, 2010)
Batch effects can lead to incorrect biological conclusions but are not widely considered. The authors show that batch effects are relevant to a range of high-throughput 'omics' data sets and are crucial to address. They also explain how batch effects can be mitigated. High-throughput technologies are widely used, for example to assay genetic variants, gene and protein expression, and epigenetic modifications. One often overlooked complication with such studies is batch effects, which occur because measurements are affected by laboratory conditions, reagent lots and personnel differences. This becomes a major problem when batch effects are correlated with an outcome of interest and lead to incorrect conclusions. Using both published studies and our own analyses, we argue that batch effects (as well as other technical and biological artefacts) are widespread and critical to address. We review experimental and computational approaches for doing so.